Short Communication: Evaluation of water quality and survival rate of red tilapia (Oreochromis niloticus) by using rice-fish culture system in quarry land of clay - DEWI HIDAYATI; SUPIANA DIAN NURTJAHYANI; DWI OKTAFITRIA; NOVA MAULIDINA ASHURI; WAHYU KURNIALLAH (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Hidayati D, Nurtjahyani SD, Oktafitria D, Ashuri NM, Kurniallah W. 2019. Short Communication: Evaluation of water quality and survival rate of red tilapia (Oreochromis niloticus) by using rice-fish culture system in quarry land of clay. Biodiversitas 20: 589-594. Quarry land is an area that has been used as mining land and has different characteristics from the former conditions before being mined so that the level of productivity of the soil decreases. This study aims to determine the suitability of clay quarry land in Tuban as a cultivation medium based on the analysis of the water quality and survival rate of red tilapia (Oreochromis niloticus) using rice-fish culture system. This study used a completely randomized experimental design method with triplicate of three ratio of cultivation medium using Ex-mining Land Soil (EmLS) from quarry land and Top Soil, i.e., 1:0 (A), 1:1 (B), and 0:1 (C/Control). Results of water quality measurements that include nitrite, nitrate, temperature, pH, and dissolved oxygen in descriptive unreal influence showed good condition. However, ammonia gives a significantly different effect mainly on the survival rate in 30 days nurture. In the end, the ANOVA test result of tilapia survival in treatment A was not significantly different (P>0.05) with treatment B and control. Based on these data, it can be seen that the EmLS from the quarry land of clay and TS can be used as a medium for cultivation of red tilapia (O. niloticus) with the recommended ratio of 1:1.